2013
DOI: 10.1073/pnas.1221701110
|View full text |Cite
|
Sign up to set email alerts
|

An experimental displacement and over 50 years of tag-recoveries show that monarch butterflies are not true navigators

Abstract: Monarch butterflies (Danaus plexippus) breeding in eastern North America are famous for their annual fall migration to their overwintering grounds in Mexico. However, the mechanisms they use to successfully reach these sites remain poorly understood. Here, we test whether monarchs are true navigators who can determine their location relative to their final destination using both a "compass" and a "map". Using flight simulators, we recorded the orientation of wild-caught monarchs in southwestern Ontario and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 36 publications
1
80
1
Order By: Relevance
“…The succession of orientation mechanisms suggested here for reef fish larvae is similar to the innate mechanisms used by birds and monarch butterflies during migration: first a compass mechanism based on global cues for the long-distance navigation phase followed by a homing process based on more local cues (e.g. [22], [24], [35], [36]). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The succession of orientation mechanisms suggested here for reef fish larvae is similar to the innate mechanisms used by birds and monarch butterflies during migration: first a compass mechanism based on global cues for the long-distance navigation phase followed by a homing process based on more local cues (e.g. [22], [24], [35], [36]). …”
Section: Discussionmentioning
confidence: 94%
“…However, thus far, no plausible mechanism has been demonstrated that could allow pelagic larvae to locate the natal reef from distances beyond a few kilometers after their initial period of passive dispersal during which they are not capable of sustained directional swimming. For longer distance directional movements, animals typically use an innate or acquired compass [18], [19], [20], [21], [22], [23], [24]. Thus, the aim of the present paper is to investigate whether reef fish larvae have a compass mechanism that could be helpful for long-distance homing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the general success of the control and VD subjects in returning to their home refuge and, more importantly, the fact that they were released on the ground indicates that amblypygids can characteristically return to their home refuge following experimental displacement to unfamiliar locations. Finally, it is worth noting that despite the impressive distance of their migration, monarch butterflies do not count among the arthropod species that can re-orient following displacement, at least during migration (Mouritsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is becoming increasingly apparent that despite their relatively small brains and generally shorter distances traveled (the monarch butterfly, Danaus plexippus, not withstanding; Mouritsen et al, 2013), many arthropod species also display an impressive navigational ability (Cheng, 2012;Collett and Graham, 2004;Boles and Lohmann, 2003;Layne et al, 2003). Indeed, both honey bees (Apis mellifera; Menzel et al, 2005) and an Australian ant species (Myrmecia croslandi; Narendra et al, 2013) have been shown to be able to return to their nests even after experimental displacement to unfamiliar locations, suggesting a cognitively rich navigational capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that migrant insects, such as the monarch, possess a map sense along with having different compass senses is unclear [13], especially given preliminary results from longitudinal displacement studies [6]. Future experiments testing the use of the magnetic compass as part of a geomagnetic map sense in monarchs, as seen in other animals that use an inclination magnetic compass [2829], can help resolve this issue.…”
Section: Magnetic Compassmentioning
confidence: 99%